Quenching Mechanisms and Kinetics of Quercetin in Inhibition of Photosensitized Oxidation of Palm Oil and Linoleic Acid - Posman Sibuea; Suparmo Suparmo; Umar Santoso; Zuheid Noor; Mary Astuti; Sri Raharjo (Indonesian Association of Food Technologists, 2004)
Effect of 0, 200, 400, 600, 800 and 1000 ppm (wt/vol) quercetin on the erythrosine sensitized photooxidations of palm oil and linoleic acid in methylene chloride containing 100 ppm erythrosine, were studied during storage under 4000 lux fluorescent light for 5 h by measuring peroxide value. Steady-state kinetic approximation was used to determine a quenching mechanism and quenching rate constant of quercetin in the erythrosine-sensitized photooxidation of palm oil and linoleic acid in methylene chloride model system. Erythrosine greatly increased the photooxidation of palm oil and linoleic acid, as was expected. Quercetin was extremely effective in minimizing erythrosine-sensitized photooxidation of palm oil and linoleic. As the concentration of quercetin increased from 0 to 200, 400, 600, 800 and 1000 ppm, the peroxide values of palm oil and linoleic acid decreased significantly (P <0.05). The steady-state kinetic studies indicated that quercetin quenched singlet oxygen only to minimize tire erythrosine-sensitized photooxidation of palm oil and linoleic acid. The calculated total quenching rate of quercetin on erythrosine photosensitized oxidation of palm oil in methtylene chloride was 4.3 x 109 M-1s-1 and total quenching rate of quercetin on erythrosine photosensitized oxidation of linoleic acid in methtylene chloride was 3.2 x 109 M-1s-1.